Resource limitation in a long-lived seabird, the Antarctic petrel Thalassoica antarctica: a twining experiment - Andersen, Reidar; Sæther, Bernt-Erik; Pedersen, Hans Christian (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1993)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

The Norwegian-British-Swedish Antarctic expedition 1949-1952 - Liljequist, Gösta H (High latitudes : a history of Swedish polar travels and research, 1993)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Documentation of the demography and population monitoring systems for Antarctic Petrels at Svarthamaren, Dronning Maud Land - Lorentsen, Svein-Håkon; Røv, Nils; Bangjord, Georg (Norsk institutt for naturforskning, 1993)
During the Norwegian Antarctic Research Expedition 1991/92, four 9 x 15 m squares for long-term demographic studies and 201 study plots for population monitoring of Antarctic Petrels Thalassatca anlarctica were established at Svarthamaren (71" 53' S, 5' 10' E), Dronning Maud Land. This report details their geographical location at Svarthamaren.
Publication Title: NINA oppdragsmelding
Keywords: Dronning Maud Land; NARE 1991/92; antarktispetrell; bestandsovervåking; fugler; ornitologi; zoologi

Digestibility of krill in crabeater seals and minke whales - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (1993)
Pages: 73 Publication Title: 10th Biennial Conference on the Biology of Marine Mammals Place: Galveston, Texas, USA
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

Satellite tracking of crabeater seals off Queen Maud Land in Antarctica - Nordøy, Erling S; Folkow, Lars P; Blix, Arnoldus Schytte (1993)
Pages: 81 Publication Title: 10th Biennial Conference on the Biology of Marine Mammals Place: Galveston, Texas, USA
Keywords: Dronning Maud Land; satellitt; seler; telemetri; zoologi

Studies of snow surface characteristics by Landsat TM in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Annals of Glaciology, 1993)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; satellittbilder